Associated factors of non-recurrence stroke among stroke patients in Thailand - Padphai, Isaree; Sripromsa, Wanida; Sanchon, Pawinee; Chotklang, Duangruedee; Wijakkanalan, Wiphada; Meelun, Nitchakarn; Ladla, Arinrada (Intelektual Pustaka Media Utama, 2024)
Stroke is a silent killer. Preventing the recurrence of strokes is therefore essential. This study investigated i) the level of health literacy to prevent the recurrence of stroke, ii) factors associated with not having a stroke, and iii) Associations between health literacy and recurrence of stroke. This cross-sectional analytical research was conducted with 240 samples. Multiple logistic regression was performed to describe the factors and associations recurrence stroke. The results showed that the majority of the samples had a problematic level of health literacy to prevent recurrence stroke (52.08%), and 35.84% had recurrence stroke. Factor: Not drinking alcohol was 6.11 times more than drinking (adj. OR=6.11, 95% CI: 4.88 to 10.04). There was no recurrence of stroke with statistical significance at the 0.05 level. High understanding skill 4.43 times (adj. OR=4.43, 95% CI=3.44 to 5.58), and high apply skill 3.67 times (adj. OR=3.67, 95% CI=2.44 to 8.18) than low and moderate levels. Statistically significant at the 0.05 level. Per findings, health literacy should be actively promoted to prevent stroke recurrence.